(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with the issues of myth-making and the relationship between the works of Ch. Aitmatov and the epic «Manas».